Laser spectroscopy and imaging applications for the study of cultural heritage murals. (15th November 2015) - Ortiz, R.; Ortiz, P.; Colao, F.; Fantoni, R.; Gómez-Morón, M.A.; Vázquez, M.A.
Highlights: LIF system scans artwork surface remotely. LIF system obtains hyperspectral fluorescence and reflectance images. Digital image analysis, PCA and SAM evaluate distribution of chemicals and damage. LIF prototype allows to scan several m 2 of a wall at 16 m of distance. Abstract: Laser induced fluorescence (LIF) associated with imaging scanning techniques has already proved to be a powerful diagnostic tool for artworks. The aim is to assess on-site and remote sensing systems and imaging measurements on murals in order to detect vulnerability and weathering forms due to the effects of environmental conditions. It also seeks to identify treatments in order to optimize interventions by restorers. Four murals (16–18th centuries) were studied using a LIF prototype remotely operating in reflectance and fluorescence mode. Relevant spectral features are identified using principal component analysis and a spectral angle mapper to assess surfaces using imaging applications. The combination of these methods makes possible to identify bio-crust, fissures and the presence of different treatments.